Assessment of the Impact of Specific Taxes on Economic Growth - Bejanyan, Hayk; Levonyan, Suren; Aghabekyan, Edgar; Davtyan, Kamo; Petrosyan, Anush («Տնտեսագետ» հրատ․)
It is clear that, as a result of consistent and accurate management of each individual type of tax, a good basis is formed for implementing an effective revenue policy of the state, which will contribute to ensuring stable economic growth. This article is dedicated to identifying the impact of state taxes, namely value added tax, income tax, profit tax, excise and sales taxes, on real GDP growth. As well as for each type of tax, the optimal level of the tax burden has been estimated, after which the impact of the tax burden changes from positive to negative. A number of statistical and econometric methods have been used to determine the size of the impact, and the Laffer curve, modified by Balatsky, has been the basis for the model evaluation. The results of the model evaluation have shown that in case of almost all tax types, the tax burden of individual tax types has a positive effect on the GDP in the period under consideration. In particular, according to the obtained results, a 1% change in income tax contributes to an average change of 0.5 percentage points in GDP, and a 1% change in profit tax contributes to an average change in GDP by 0.23 percentage points. The impact of the excise tax is also positive and a 1% change in the latter leads to a 0.42 percentage point change in GDP.
Keywords: Finance